Müzik Dersi Öğretim Programının Avrupa Yeterlilikler Çerçevesi ve Türkiye Yeterlilikler Çerçevesi Açısından İncelenmesi - Özgül, İlhan (OPUS - Uluslararasi Toplum Arastirmalari Dergisi, 2021)
The 2018 Music Course Curriculum was examined within the scope of the key competencies of the European Qualifications Framework (AYC) and the Turkish Qualifications Framework (TQF) in this study. Document analysis, one of the qualitative research approaches, was employed in the study. Special objectives of the 2018-Music Course Curriculum, field-specific skills, the achievements defined for grades 1-8, and the relationship of the four learning areas with the key competencies determined within the scope of Turkish Qualifications Framework (TQF) and European Qualifications Framework (EQF) were investigated. It has been tried to determine the main similarities and differences between the Music Course Curriculum in Turkey and the Music Curriculum of European schools. According to the findings, considering the relationship between “special goals”, “field-specific skills”, “achievements covering grades 1-8” and “Learning Areas” defined in the Music Course Curriculum and the key competencies as a whole, competence areas related with learning to learn, communication in the mother tongue, cultural awareness and expression, social and citizenship are included at most. It has been determined that while some areas included less such as taking initiative and entrepreneurship, digital competence, mathematical competence and competence in science and technology, the competence of "communication in foreign languages" is not included at all. Comparing the Music Course Curriculum and the European Schools Music Curriculum, it is seen that the music listening activities in the 2018-Music Curriculum are in the nature of listening activities held/organized to create a "cultural awareness" in students, rather than a purposeful listening on the basic concepts and applications of music teaching methodology and also it has been determined that the achievements of "playing an instrument" are not included. Recommendations are given regarding the reorganization/correction of the deficiencies that may be considered important in terms of curriculum development in the 2018-Music Course Curriculum prepared within the scope of the Turkish Qualifications Framework (TQF), a member of the European Qualifications Framework (EQF).

Bu araştırmada, 2018 Müzik Dersi Öğretim Programı, Avrupa yeterlikler Çerçevesi (AYÇ) ve Türkiye Yeterlikler Çerçevesi (TYÇ) anahtar yetkinlikleri kapsamında incelenmiştir. İnceleme sürecinde nitel araştırma yaklaşımlarından doküman incelemesi kullanılmıştır. Çalışmada, 2018-Müzik Dersi Öğretim Programının özel amaçları, alana özgü beceriler, 1-8 sınıflar için tanımlanan kazanımlar ve dört öğrenme alanının Türkiye Yeterlilikler Çerçevesi (TYÇ) ve Avrupa Yeterlilikler Çerçevesi (AYÇ) kapsamında belirlenen anahtar yetkinlikler ile ilişkisi araştırılmıştır. Müzik Dersi Öğretim Programı ile Avrupa Okulları Müzik Öğretim Programı arasındaki temel benzerlik ve farklılıklar belirlenmeye çalışılmıştır. Elde edilen bulgulara göre, Müzik Dersi Öğretim Programında tanımlanan “özel amaçlar”, “alana özgü beceriler”, “1-8 sınıfları kapsayan kazanımlar” ve “Öğrenme Alanları” ile anahtar yetkinliklerin İlişkisi bir bütün olarak incelendiğinde, en çok öğrenmeyi öğrenme, anadilde iletişim, kültürel farkındalık ve ifade, sosyal ve vatandaşlıkla ilgili yetkinlik alanlarına yer verilmiştir. İnisiyatif alma ve girişimcilik, dijital yetkinlik, matematiksel yetkinlik ve bilim teknolojide yetkinlik alanlarına daha az yer verilirken, “Yabancı dillerde iletişim” yetkinliğine hiç yer verilmediği tespit edilmiştir. Müzik Dersi Öğretim Programı ile Avrupa okulları müzik öğretim programı karşılaştırıldığında 2018-Müzik dersi öğretim programında müzik dinleme etkinlikleri müzik öğretimi metodolojisinin temel kavramları ve uygulamalarına ilişkin amaçlı dinleti yapmaktan ziyade öğrencilerde bir “kültürel farkındalık” yaratmak üzere yapılan/düzenlenen dinletiler niteliğinde olduğu, öğrenme alanlarında “çalgı çalma” kazanımlarına yer verilmediği tespit edilmiştir. Avrupa Yeterlikler Çerçevesinin (AYÇ) bir üyesi olan Türkiye Yeterlikler Çerçevesi (TYÇ) kapsamında hazırlanan 2018-Müzik Dersi Öğretim Programının program geliştirme açısından önemli görülebilecek eksikliklerin yeniden düzenlenmesi/düzeltilmesine ilişkin öneriler getirilmektedir.
Keywords: Alan Eğitimleri; Müzik Dersi Öğretim Programı; AYÇ; TYÇ; Anahtar Yetkinlikler; Music Course Teaching Program; TQF; EQF; Key Competencies; Other Fields of Education; 4. Education